A produção dos sentidos do humor nos cartuns de Maitena: um estudo linguístico-discursivo - Costa, Marisa da (2011)
This essay is related to the Research Field Text and Discourse in spoken and written modalities of Portuguese Language Post-graduate Studies Program. It has the target to examine the linguistic-discoursive resources which appear on Maitena‟s cartoons, aiming the production of the meaning of the text and, therefore, the comicality present in it. As a presupposed there is the interactional language conception, which recognizes the reader as an active subject, who participates in building the text sense. Cartoons are a discoursive genre constituted by verbal and non-verbal text, which main characteristic is atemporality and universal set of themes, and have the communicative proprosal of promoting a social reflection with a certain grade of humour. To achieve our target, we present a broad view of other genres that use the iconic-verbal language aiming to better situate cartoon as our object of study. The theories presented by Possenti (2008), Travaglia (1990), and Rosas (2002) stresses the importance of humouristic text as a source of language research. Our essay contributes, thus, as a reinforcement to these author‟s ideas in the way it explores linguistic and discoursively the genre in question